Oral Cancer Knowledge and Screening Practices Among Dental Professionals in Yemen: a Web-Based Survey - Sadeq Ali Al-Maweri; Esam Halboub; Anas Shamala; Abdulrazzaq Ahmed Al-Maweri; Alaa Daud; Ebrahim Almurisi; Asma Saleh Almeslet; Saba Kassim; Mohammed Nasser Alhajj (International Dental Journal)
Background: Good knowledge and screening practices of dental professionals for oral cancer (OC) will inevitably improve its prognosis. The present study sought to evaluate OC knowledge and practices among dental professionals in Yemen. Methods: This study was conducted among Yemeni dentists. The used tool was a prevalidated online questionnaire composed of items on the knowledge, practices, and barriers of OC screening and early detection. The data were managed and analysed using SPSS Version 28.0. Results: A total of 506 dental professionals completed the questionnaire. The participants showed moderate levels of knowledge on risk factors and clinical signs of OC. While the majority reported tobacco (89.9%) as a potential risk factor, only 76.7% and 57.5% of the subjects reported a potential role for alcohol consumption and old age. Regarding clinical signs, the majority reported that OC can present as nonhealing ulcer (90.3%) or white/red patch (87.2%), yet only 73.7% reported that it can present as swelling/lump, and around 32% reported that teeth attrition is one of its clinical signs. Concerning practices, most of the participants reported asking their patients about their tobacco habits (84%), routinely examine patients’ oral mucosa (81.4%), and refer suspicious lesions to specialists (91.3%). Only 44.9% reported feeling confident regarding their knowledge and training on OC. Specialists and those who attended educational courses on OC were more knowledgeable, more confident, and showed better practices than their counterparts. Inadequate knowledge/training, lack of time, and lack of financial compensation were the most reported barriers to OC screening and early detection. Conclusion: The present study indicates marked gaps in the knowledge and screening practices of OC among Yemeni dentists. Therefore, conducting periodic continuing courses along with interventional trainings are urgently recommended to address these gaps.